2018
DOI: 10.1038/s41598-018-20016-w
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of novel mutations in the pSC101 origin that increase copy number

Abstract: pSC101 is a narrow host range, low-copy plasmid commonly used for genetically manipulating Escherichia coli. As a byproduct of a genetic screen for a more sensitive lactam biosensor, we identified multiple novel mutations that increase the copy number of plasmids with the pSC101 origin. All mutations identified in this study occurred on plasmids which also contained at least one mutation localized to the RepA protein encoded within the origin. Homology modelling predicts that many of these mutations occur with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Both ColE1 derivatives and RK2 origins have been shown to be targeted to specific subcellular locations near midcell (39). The pSC101 origin uses a Rep initiator protein to bind intron regions controlling replication and includes a partitioning locus to stabilize inheritance (40). In our previous study, we observed that plasmids with different origins were transferred by EVs at differing rates (12), although the plasmids compared previously were of various sizes.…”
mentioning
confidence: 93%
“…Both ColE1 derivatives and RK2 origins have been shown to be targeted to specific subcellular locations near midcell (39). The pSC101 origin uses a Rep initiator protein to bind intron regions controlling replication and includes a partitioning locus to stabilize inheritance (40). In our previous study, we observed that plasmids with different origins were transferred by EVs at differing rates (12), although the plasmids compared previously were of various sizes.…”
mentioning
confidence: 93%
“…In addition, we also optimized other terms, including the concentrations of L-arabinose and IPTG, the culture time, and the medium to further improve the system's performance (Table S6). At an appropriate concentration of L-arabinose, the expression levels of Cas9 and sgRNA were enough for cleaving the single-copy genome, but insufficient for cleaving all copies of plasmid#2 (about five copies [31]). Therefore, edited cells still possessed resistance to Amp.…”
Section: Optimization Of Crispr/cas9-assisted Recombineering Methodsmentioning
confidence: 99%
“…Plasmid confirmation via MiSeq sequencing. Plasmid deep sequencing was performed as in previous work 50 . E. coli KCM competent cell prep.…”
Section: Methodsmentioning
confidence: 99%